2021
DOI: 10.3390/act10020020
|View full text |Cite
|
Sign up to set email alerts
|

Active Disturbance Rejection Control for Position Tracking of Electro-Hydraulic Servo Systems under Modeling Uncertainty and External Load

Abstract: In this paper, an active disturbance rejection control is designed to improve the position tracking performance of an electro-hydraulic actuation system in the presence of parametric uncertainties, non-parametric uncertainties, and external disturbances as well. The disturbance observers (Dos) are proposed to estimate not only the matched lumped uncertainties but also mismatched disturbance. Without the velocity measurement, the unmeasurable angular velocity is robustly calculated based on the high-order Levan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…It arranges the appropriate transition process by using the tracking differentiator (TD). The differential tracker can be expressed as [28,29]:…”
Section: 2 Design Of the Active Disturbance Rejection Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…It arranges the appropriate transition process by using the tracking differentiator (TD). The differential tracker can be expressed as [28,29]:…”
Section: 2 Design Of the Active Disturbance Rejection Controllermentioning
confidence: 99%
“…The improved sliding mode control law is progressively stable. The specific proof that the tracking differentiator is stable in a finite time is given in paper [28]. Due to space limitations, i will not repeat it.…”
Section: Stability Analysis Of Controllermentioning
confidence: 99%
“…is the average piston area; It is the ratio coefficient of the area of the two cavities and the mean value of the equivalent volume of the hydraulic cylinder; Is the equivalent area, is the hydraulic cylinder stroke. By solving equation ( 6), equation (7) and equation ( 10) simultaneously, it can be concluded that:…”
Section: Figure 2 Schematic Diagram Of Valve-controlled Asymmetric Hydraulic Cylindermentioning
confidence: 99%
“…In addition to chattering, it is usually required to know the model uncertainties and the limit value of disturbance in the design process of the SMC [31]. However, in practice, the limit value is not always obtainable [32]. Even after disturbance compensation, the limit value of disturbance compensation error is not easy to obtain.…”
Section: Introductionmentioning
confidence: 99%